Two new chironomid species of the genus Pseudokiefferiella Zavřel (Diptera: Chironomidae: Diamesinae) from the Amur River basin of Russia - Makarchenko, Eugenyi A.; Semenchenko, Alexander A. (Zootaxa, 2023)
The adult male, pupa, larva with DNA barcoding of Ps. matafonovi sp. nov. and the adult male of Ps. silinka sp. nov. from Amur River basin of Russia are described and illustrated. Ps. matafonovi sp. nov. is genetically distant from other Pseudokiefferiella showing uncorrected p-distances of >6.8 %. The results of species delimitation show that genus Pseudokiefferiella includes 10 (mPTP), 13 (ASAP, GMYC) or 14 (BOLD) distinct molecular taxonomic units (mOTUs) that requires a revision of this genus using both morphological and molecular approaches.